Analisis Nilai SO2 dan NO2 Cerobong Emisi pada Industri Peleburan Baja Kabupaten Bekasi - Daningsih, Woro Wur; Wangitan, Roy; Febrina, Laila; khasanah, fata nidaul (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2025)
PT X operates in the steel smelting and rolling industry (Furnace & Steel Rolling). The purpose of this study is to examine the steel smelting production process at PT X that has the potential to generate emissions, to identify PT X’s emission control processes, to assess the measurement results of particulate, opacity, SO₂, and NO₂ parameters from steel smelting, and to analyze whether PT X’s emissions comply with the emission quality standards. Steel smelting activities are a major source of NOx, SOx, and particulate formation. The use of raw materials such as pig iron, cast iron, and hot briquetted iron, which contain sulfur levels ranging from 0.05–0.15%, serves as the main source of SOx emissions. The injection of pure nitrogen and pure oxygen into the electric arc furnace contributes to NOx emissions. The results of stack gas emission testing at PT X showed maximum levels of 47 mg/m³ for particulates, <20% for opacity, 76 mg/m³ for SO₂, and 11.49 mg/m³ for NO₂ during the period from the second quarter of 2024 to the first quarter of 2025.